2005
DOI: 10.1211/jpp.57.9.0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-piperidinomethyl-2-isopropyl-5-methylphenol on oxidative stress and calcium current

Abstract: 4-Piperidinomethyl-2-isopropyl-5-methylphenol (THPI) was synthesized by reaction of thymol with piperidine and formaldehyde. The biological effect of THPI on superoxide anion scavenging activity, antiplatelet activity and calcium current inhibition were investigated. THPI (50 microM) was shown to be a scavenger of superoxide radicals in human neutrophils stimulated with N-formyl-Met-Leu-Phe (66% inhibition). Since superoxide anions are essential for platelet aggregation and L-type Ca2+-channel activity, we fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(28 reference statements)
0
7
1
Order By: Relevance
“…The results suggest that the binding site of this compound was distinguishable from that of 1-EBIO and could be located in the (Jensen et al 2001;Stocker 2004), it remains to be determined to what extent THPI exerts an inhibitory effect on small-conductance K Ca channels. Previous studies have shown the ability of THPI to block L-type Ca 2+ current in NG108-15 neuronal cells (Huang et al 2005). In this study, there was no evidence to show the presence of voltage-gated Ca 2+ or Na + channels in HL-60 cells.…”
Section: Effects Of Thpi On Cytoprotective Activitycontrasting
confidence: 77%
See 2 more Smart Citations
“…The results suggest that the binding site of this compound was distinguishable from that of 1-EBIO and could be located in the (Jensen et al 2001;Stocker 2004), it remains to be determined to what extent THPI exerts an inhibitory effect on small-conductance K Ca channels. Previous studies have shown the ability of THPI to block L-type Ca 2+ current in NG108-15 neuronal cells (Huang et al 2005). In this study, there was no evidence to show the presence of voltage-gated Ca 2+ or Na + channels in HL-60 cells.…”
Section: Effects Of Thpi On Cytoprotective Activitycontrasting
confidence: 77%
“…THPI (4-piperidinomethyl-2-isopropyl-5-methylphenol) was synthesized by methods as described previously (Huang et al 2005). Mitomycin C was purchased from Sigma-Aldrich (St Louis, MO, USA).…”
Section: Drugs and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been observed that thymol suppresses transmembrane calcium and potassium currents [52,53] in a concentration-dependent manner through ion channels such as voltage-dependent sodium channels [54] , and inhibits the activity of L-type calcium channels [52][53][54][55][56] by inhibiting capacitative calcium entry. The substituents of the benzene ring in aromatic molecules influence electron distribution and thus affect their physicochemical properties, particularly lipid solubility [59] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the compounds having phenol functional group are known to have anticancer, antibacterial, antiviral, antifungal and antioxidant activities [7][8][9] . Thymol, 2-isopropyl-5-methylphenol, is a bioactive natural phenolic compound which was isolated from Thymus sulgaris Thymol is known to show antioxidant [11][12][13] , anticancer 14,15 , antidepressant 16 , antibacterial 17,18 C NMR (100 MHz) spectra were taken using a Varian Mercury Plus spectrometer (Varian Inc., Palo Alto, CA). Chemical shifts (d) were reported in ppm.…”
Section: Introductionmentioning
confidence: 99%